A new species of Afroarabiella Yakovlev, 2008 (Lepidoptera, Cossidae) from the Republic of South Africa, including a world catalogue of the genus - Yakovlev, Roman V. (Zootaxa, 2014)
The genus Afroarabiella Yakovlev, 2008 (Lepidoptera: Cossidae) was established for Cossus tahamae Wiltshire, 1949 by Yakovlev (2008). Currently, seven species are included in the genus (Yakovlev 2008). Yakovlev (2011) added an additional new species, A. tanzaniae Yakovlev from Tanzania. Members of the genus are widespread from the southwestern Arabian Peninsula and throughout much of Africa (Fig. 1). During the studies of Lepidoptera by Petr Ustjuzhanin (Novosibirsk, Russia) and Vasilij Kovtunovich (Moscow), a new species of the genus Afroarabiella was discovered and the description is given below.